One-Pot Template-Free Hydrothermal Synthesis of Monoclinic Hollow Microspheres and Their Enhanced Visible-Light Photocatalytic Activity - Bei Cheng; Wenguang Wang; Lei Shi; Jun Zhang; Jingrun Ran; Huogen Yu (International Journal of Photoenergy)
Monoclinic-phase BiVO4 hollow microspheres with diameters of about 2–4 μm have been successfully fabricated in high yield by a one-pot template-free hydrothermal route. The reaction duration and urea concentration are shown to play important roles in the formation of the BiVO4 hollow microspheres. X-ray diffraction, scanning electron microscopy, nitrogen adsorption-desorption isotherms, fourier transform infrared spectrometry, and UV-visible diffuse reflectance spectroscopy are used to characterize the products. The results show that all the as-prepared BiVO4 samples have monoclinic phase structure and exhibit good crystallinity. A formation mechanism for the BiVO4 hollow spherical structure via a localized Ostwald ripening is proposed based on the experimental observations. In addition, studies of the photocatalytic properties by exposure to visible light irradiation demonstrate that the as-obtained BiVO4 hollow spheres show potential photocatalytic application. Hydroxyl radicals (•OH) are not detected on the surface of visible-light-illuminated BiVO4 by the photoluminescence technique, suggesting that •OH is not the dominant photooxidant and photogenerated hole could directly take part in photocatalytic reaction. The prepared BiVO4 hollow spheres are also of great interest in pigment, catalysis, separation technology, biomedical engineering, and nanotechnology.